Development of multiple taliks near settlements on Svalbard – a new source of drinking water for the High Arctic? - Sinitsyn, Anatoly O.; Bazin, Sara; Benestad, Rasmus; Etzelmüller, Bernd; Isaksen, Ketil; Kvitsand, Hanne; Lutz, Julia; Popp, Andrea L.; Rubensdotter, Lena; Westermann, Sebastian (Copernicus Publications, 2023)
This article presents a comprehensive documentation and analysis of long-term observations of year-round groundwater occurrences in rivers and various types of taliks under continuous permafrost conditions on Svalbard. Previously thought to be nonexistent, the existence of these taliks has been confirmed through rigorous field observations, geotechnical investigations, and extensive data collection. This discovery holds pivotal implications for our current understanding of permafrost conditions in central Svalbard. The research reveals the presence of several year-round taliks in close proximity to the settlements in Longyearbyen, Pyramiden, and Ny-Ålesund. Importantly, these findings open up opportunities for using these taliks as groundwater reservoirs for extraction of drinking water, either in natural state or with appropriate engineering modifications. Furthermore, climate change may the possibilities in future by expanding the size of these talik reservoirs due to rising air temperatures and increased inflow of fresh water over prolonged summer . The results underscore the importance of including river taliks in continuous permafrost areas in water management strategies for Svalbard and similar Arctic regions. This research not only challenges prior assumptions but also offers valuable insights for sustainable water resource utilization in a changing climate context.